Perspectives on Community Well-Being - Kee, Youngwha; Lee, Seung Jong; Phillips, Rhonda (Community Quality-of-Life and Well-Being, 2019)
This volume brings together multiple diverse perspectives from around the globe on quality of life and community well-being from a place-based perspective. It provides both conceptual and applied explorations across disciplines, ideas and perspectives to foster more interest and research in community well-being. Topics include surveying at the community level, child friendly communities, collective impact, grieving, and happiness. Those working in the areas of public policy, community development, community and social psychology, as well as planning and development will find this volume particularly useful for the array of perspectives, research, and analytical approaches presented. .